Effect of injector geometry in breakup of liquid jet in crossflow – insights from POD - Sinha, Anubhav (Elsevier Ltd, 2023)
The present study investigates the role of injector geometry, particularly injector tube length-to-diameter ratio (L/D), in liquid jet stability and breakup in the presence of crossflow. Water is injected into a crossflow of air. Aerodynamic Weber number (Weg) and liquid Reynolds number (Rel) are systematically varied to observe various breakup modes. High-resolution images are captured for the near-nozzle region. Transition to turbulence is found to be affected by the nozzle geometry. Column breakup and surface stripping are observed for different operating conditions. A regime map is proposed based on the present observations. Time-resolved jet trajectory images are processed using Proper Orthogonal Decomposition (POD) algorithm. POD mode shapes and corresponding Power Spectral Density (PSD) plots are analyzed to study the breakup process and probe the role of injector geometry effects. A detailed comparison is made for various cases. It is observed that with an increase in (L/D), the jet surface becomes more turbulent and unstable, which results in an early breakup and lower jet penetration.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Geometry; Jets; Principal component analysis; Reynolds number; Spectral density